Toward Functional Synthetic Cells: In‐Depth Study of Nanoparticle and Enzyme Diffusion through a Cross‐Linked Polymersome Membrane. Issue 7 (11th January 2019) - Gumz, Hannes; Boye, Susanne; Iyisan, Banu; Krönert, Vera; Formanek, Petr; Voit, Brigitte; Lederer, Albena; Appelhans, Dietmar
Abstract: Understanding the diffusion of nanoparticles through permeable membranes in cell mimics paves the way for the construction of more sophisticated synthetic protocells with control over the exchange of nanoparticles or biomacromolecules between different compartments. Nanoparticles postloading by swollen pH switchable polymersomes is investigated and nanoparticles locations at or within polymersome membrane and polymersome lumen are precisely determined. Validation of transmembrane diffusion properties is performed based on nanoparticles of different origin—gold, glycopolymer protein mimics, and the enzymes myoglobin and esterase—with dimensions between 5 and 15 nm. This process is compared with the in situ loading of nanoparticles during polymersome formation and analyzed by advanced multiple‐detector asymmetrical flow field‐flow fractionation (AF4). These experiments are supported by complementary i) release studies of protein mimics from polymersomes, ii) stability and cyclic pH switches test for in polymersome encapsulated myoglobin, and iii) cryogenic transmission electron microscopy studies on nanoparticles loaded polymersomes. Different locations (e.g., membrane and/or lumen) are identified for the uptake of each protein. The protein locations are extracted from the increasing scaling parameters and the decreasing apparent density of enzyme‐containing polymersomes as determined by AF4. Postloading demonstrates to be a valuable tool for the implementation of cell‐like functions in polymersomes. Abstract : For integrating cell‐like functions in polymersomes, control over nanoparticle locations (membrane, lumen of polymersomes, and/or inner/outer membrane surface) is demonstrated by a postloading approach of swollen polymersomes. The softness of nanoparticles for crossing polymersomes membrane is the major key issue, while the size and charge of nanoparticles mainly plays a minor role.